2006
DOI: 10.1021/ol061642f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a New Cross-Linkable Perfluorocyclobutane-Based Hole-Transport Material

Abstract: [reaction: see text] A new curable arylamine containing a perfluorocyclobutane (PFCB) structure without an acidic group was synthesized. The material was thermally cured on ITO after spin-coating. The polymer showed excellent solvent resistance, high thermal stability, high transparency, and good surface smoothness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 39 publications
1
47
0
Order By: Relevance
“…In OSCs, poly (3,4-ethylenedioxythiopene): poly(styrene sulfonate) (PEDOT:PSS) is widely used as the hole transport layer (HTL) for the following reasons: hole-only transport (electron blocking) [7], improved smoothness of the indium-tin oxide (ITO) anode surface [8,9], and the appropriate energy level alignment of the work function of PEDOT:PSS between the anode and active layer. However, the acidic property of PEDOT:PSS leads to corrosion of the ITO layer and results in diffusion of In and Sn from the corroded ITO into the active layer, which induces the degradation of OSCs [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In OSCs, poly (3,4-ethylenedioxythiopene): poly(styrene sulfonate) (PEDOT:PSS) is widely used as the hole transport layer (HTL) for the following reasons: hole-only transport (electron blocking) [7], improved smoothness of the indium-tin oxide (ITO) anode surface [8,9], and the appropriate energy level alignment of the work function of PEDOT:PSS between the anode and active layer. However, the acidic property of PEDOT:PSS leads to corrosion of the ITO layer and results in diffusion of In and Sn from the corroded ITO into the active layer, which induces the degradation of OSCs [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is very important to get some insights to control the hole injection from the anode in the devices. Until now, molecular interface engineering between the anode and the emitting layer (EML) has been done by chemical modification of the anode [3][4][5] or introducing a polymeric hole-injection layer (HIL) [6][7][8][9][10] . Hole-injecting conducting polymer films such as polyaniline and poly(3,4-ethylenedioxy thiophene) (PEDOT) doped with a polymeric sulfonic acid on indium tin oxide (ITO) layer has been employed because they can improve the hole injection from the ITO (work function: $ 4.7-5.0 eV) and planarize the ITO surface.…”
Section: Introductionmentioning
confidence: 99%
“…Hole-injecting conducting polymer films such as polyaniline and poly(3,4-ethylenedioxy thiophene) (PEDOT) doped with a polymeric sulfonic acid on indium tin oxide (ITO) layer has been employed because they can improve the hole injection from the ITO (work function: $ 4.7-5.0 eV) and planarize the ITO surface. [9] A generally used polymeric HIL is composed of PEDOT and polystyrene sulfonate (PSS), called as PED-OT:PSS, which is commercially available from H. C. Starck. GmbH.…”
Section: Introductionmentioning
confidence: 99%
“…To date, these semi-fluorinated polymers have only been used as hole-transport layers, due to their ease of processing and thermal polymerization and chemical resistance; as compared with the conventional PEDOT:PSS layer. Jen and co workers [97][98][99][100][101][102][103][104][105] showed that PFCB aryl ether polymers functionalized with hole-transport components, for example 21, has identical or better performance, as well as high transmission in the entire visible spectrum. One noteworthy example utilizing crosslinked PFCB aryl ether polymer such as 23 was as a gate dielectric for organic thin film transistors (OTFTs), showing a high on/off ratio.…”
Section: Polymer Light Emitting Diodesmentioning
confidence: 99%